Multiple glomuvenous malformations presenting in a child: follow-up over a period of 8 years - Jabir, Shehab (BMJ Publishing Group, 2013)
Multiple glomuvenous malformations (GVMs) are a rare condition which usually present in children with only a handful of cases reported in the literature. It is usually congenital and has an autosomal dominant inheritance pattern. They may be distributed throughout the body in either a localised, segmental or disseminated pattern. Pain, which is a characteristic feature of glomus tumours, is less often associated with GVMs. In addition, unlike glomus tumours which most commonly occur over acral skin surfaces, GVMs may occur throughout the body. A number of treatment options are available including surgical excision, laser treatments and sclerotherapy. We present the case of a 14-year-old boy with multiple GVMs which were treated with surgical excision and followed him up over a period of 8 years.